Vertical and oblique ionospheric soundings over the long haul HF link between Antarctica and Spain. Issue 9 (29th September 2015) - Ads, A. G.; Bergadà, P.; Regué, J. R.; Alsina‐Pagès, R. M.; Pijoan, J. L.; Altadill, D.; Badia, D.; Graells, S.
Abstract: This paper presents a comparative study between the oblique sounding results, the International Telecommunication Union Rec533 HF prediction model, and the vertical sounding results of a transequatorial long haul link. The long haul link is a 12, 760 km link between the Spanish Antarctic Station, SAS, located in the Livingston Island and the Ebro Observatory (OE) in Spain. The data were collected during three consecutive surveys (2009/2010, 2010/2011, and 2011/2012). The ionospheric channel from the SAS to the OE is studied in terms of frequency availability as function of time using the measurements of an oblique incidence sounder (OIS) and measurements of several vertical incidence sounding stations (VIS) placed near the estimated radiopropagation path. The results obtained show promising correlations between VIS and OIS measurements and led us to think that the frequency of largest availability for this particular long haul radio link can be estimated from the VIS sounding measurements. Key Points: Comparison between the OIS, the ITU Rec533 HF prediction model, and the VIS of a transequatorial link The channel is studied in terms of frequency availability as function of time